A Case Study on Children Marketing of KFC - Ang, Sae Ming (1999)

(untitled)
Children are the important customers to any one of fast· food chain, simply because children will not visit restaurant alone, but go along with family members or having a party there with a group of friends, this translate into sales to restaurants. When the American fast food were later introduced to other part of the world, other brand of fast food chain follow the tracked and flourished oversea as well, the battle ground since then happened everywhere, the fittest fight for market leadership, the others aimed for survival KFC came to Malaysia in 1973, since then expanded aggressively and had transformed into integrated food corporation, however, with 275 outlets, KFC still operates chicken fast food core business, the near competitor is McDonalds' which has about 120 restaurants. The competition is always tense, because, Malaysia and Thailand are the only two countries that McDonalds loose to KFC. Knowing McDonalds is strong in Kids Marketing, KFC Malaysia set up own the first Children Marketing team which only focus children related activities. Over year, children marketing performance are quite acceptable, as many promotions, toys, children magazine, outdoor activities were organized. Sales generated still below the projection, though it is recognized that the purpose of children marketing is for longterm loyalty and brand building. However, when the company undergone ownership change, children marketing strategy is reviewed, the unit needs to be revamped to have new direction and strategy. The first part is basically the case, followed by analysis on the 2nd part, the second too accompanied with Strategy formulation, implementation and control evaluation.